Governing orders at odds in Sápmi - Grönvall, Agnes (2019)
The Sami people, an indigenous people in Scandinavia, and their cultural practice of reindeer herding have been divided across the northern parts of Sweden, Norway, Finland, and north-western Russia, since the national borders were established in the 1700-1800s. In Sweden and Norway, trans-border reindeer herding (TBRH) has been regulated by several bilateral agreements, but from 2005 the countries have failed to negotiate a new convention for TBRH. As a consequence, different opinions regarding what regulations are in fact, or should be, in force today result in a conflicting situation for those who practice TBRH. In a collaboration with Saarivuoma reindeer herding community (RHC), I use social impact assessment as a tool to investigate how impacts from previous and present TBRH regulations are perceived today. I used Kooiman’s interactive governance framework to analyse how these impacts relate to first order of governance. The results show that for Saarivuoma RHC bilateral conventions of TBRH have meant that they had to adapt to a static and rigid reindeer herding practice, which lowered their problem-solving capacity. Since 2005 they have instead followed regulations in the Lapp codicil from 1751. This meant a more dynamic and flexible reindeer herding practice and regaining of cultural traditions, and thus an increased capacity for problem-solving. Failed negotiations between Sweden and Norway could be seen as a governing failure. However, failed negotiations instead led to increased problem-solving capacity for Saarivuoma RHC, illustrating that the institutional level has hampered rather than helped the operational level to solve societal challenges facing reindeer herding.